Accusatory and exculpatory moves in the hunting for "Racists" language game. (March 2016) - Hodges, Adam
Abstract: Race talk in the US frequently singles out individuals as "racists, " positioning them as outliers in a society that has supposedly moved beyond race. However, this type of "language game" is premised upon a narrow understanding of racism that reduces it to individual bigotry while ignoring its systemic dimensions. This article examines the accusatory and exculpatory moves in this language game by analyzing three cases that received mainstream media attention. The analysis shows that the discursive moves ultimately work to reproduce dominant ideological assumptions, doing more to protect white privilege than to dismantle racism. This occurs even as speakers engage in ostensibly anti-racist talk. Highlights: Race talk in the US often singles out individual "racists" as societal outliers. This discourse relies upon and reproduces a narrow understanding of racism. Both accusatory and exculpatory moves reproduce dominant ideological assumptions. This occurs even as speakers engage in ostensibly anti-racist talk.